2021
DOI: 10.18087/cardio.2021.2.n1472
|View full text |Cite
|
Sign up to set email alerts
|

Approach to decongestion therapy in patients with acute decompensated heart failure: the echocardiography guided strategy

Abstract: Goal The E / (Ea×Sa) index is an echocardiographic parameter to determine a patient’s left ventricular filling pressure. This study aims to determine the safety and efficacy of the echocardiographic E / (Ea×Sa) index guided diuretic therapy compared to urine output (conventional) guided diuretic treatment.Material and Methods In this cross-sectional study, patients with heart failure with reduced ejection fraction (HFrEF) who were hospitalized due to acute decompensation episode were consecutively allocated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The endpoint studied in this study was the change in serum creatinine levels as a marker of kidney injury; however, there was a huge difference in baseline kidney function among the two groups (serum creatinine levels were 3.25 in the UF group vs. 1.75 in the diuretics group), and therefore the initial categorization of patients among groups seemed problematic. Another study [39] which was identified in our first search of literature and was translated from Russian but was not included as well because of issues in randomization process. Although it was described as a randomized control trial, there was no clear description of the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The endpoint studied in this study was the change in serum creatinine levels as a marker of kidney injury; however, there was a huge difference in baseline kidney function among the two groups (serum creatinine levels were 3.25 in the UF group vs. 1.75 in the diuretics group), and therefore the initial categorization of patients among groups seemed problematic. Another study [39] which was identified in our first search of literature and was translated from Russian but was not included as well because of issues in randomization process. Although it was described as a randomized control trial, there was no clear description of the process.…”
Section: Discussionmentioning
confidence: 99%
“…For the outcome of weight change, four studies were excluded from our analysis. Two of these studies [28, 38] had fewer than 10 patients in each arm and the other two [37, 39] compared practically different populations as we described in detail above. In disagreement with our finding, in this review, the weight change was calculated as an absolute, positive number in three of these studies which resulted in a weight change in favor of diuretics.…”
Section: Discussionmentioning
confidence: 99%